Maternal Anaemia Is An Independent Risk Factor For Preterm Labour (Journal of Fatima Jinnah Medical University, 2018)
INTRODUCTION: Anemia is the main hematological complication during pregnancy. Over the world, anemia during pregnancy is a public health problem. Low folic acid intake increases the risk for preterm delivery.OBJECTIVE: To determine the association between maternal anemia and preterm labour.STUDY DESIGN: Cross-sectional studySETTING: Obstetric and Gynaecology Department, Sir Ganga Ram Hospital, LahoreDURATION OF STUDY: Study was carried out over a period of six months from 01st January 2009 to 30th June 2009MATERIAL AND METHOD: Total 280 antenatal laboring patients, of which 140 between 24 and 37 weeks of gestation (group-A), remaining 140 >37 weeks of gestation (group-B) were selected.RESULTS: Regarding distribution of cases be age, majority of the patients were between 21-25 years i.e. 73(52.1%) and 77 (55.0%) in group-A and B, respectively. Minimum patients were between 31-35 years of age, in group-A (8.3%) and in group-B, 5 patients (3.6%) with mean age 28.3+_ 5.1 and 29.5+_3.7 in group-A and B respectively. 71 (50.7%) preterm laboring were anemic, the remaining 69 (49.3%) were not anemic. 39 (27.9%) of term labouring patients were anemic while 101 (72.1%) were not.CONCLUSION: The study concludes that anemia has got a significant effect on the occurance of preterm labour.
Keywords: Maternal anemia, preterm labour, nutrition.